Impact of Traditional Behavior of Customers, Employees, and Social Enterprises on the Fear of Change and Resistance to Innovation - Liu, Xiaoyan; Wang, Fei; Wong, CheeHoo (Frontiers in Psychology, 2022)
Innovation adoption is the necessary element for the success of any organization around the globe, and this phenomenon needs the foremost solution. The current article examines this area and explores the impact of customers, employees and social enterprises’ traditional behavior on the resistance to innovation in social enterprises in China. The current article also investigates the mediating role of fear for change among customers, employees and social enterprises’ traditional behavior and resistance to innovation in social enterprises in China. This article has followed the primary data gathering methods and adopted the questionnaires for this purpose. The present research has also applied the SPSS-AMOS to analyze the association among variables and test the hypotheses. The results revealed that the traditional behavior of customers, employees, and social enterprises has a significant and positive linkage with resistance to innovation in social enterprises in China. The findings also exposed that the fear of change also significantly mediates among customers, employees and social enterprises’ traditional behavior and resistance to innovation in social enterprises in China. This article helps the regulators establish policies related to innovation adoption by changing traditional behavior to advance the behavior of customers, employees, and social enterprises.